Medios de comunicación local y comportamiento social - Andrade Arauz, Milena Janina (2022)
This investigative and journalistic work sought to probe, evaluate and show how young people tend to change their behavior because they are influenced either by culture, attitudes, or by following different fashions. Therefore, the main objective of this project is to study and determine if there is an influence on the behavior of the digital media La Unik.TV and Naranjal TV in young people between 18 and 25 years of age from the Las Cruces neighborhood of the Naranjal canton. For the development of this research work, research techniques (interview, survey and observation) were applied, through these techniques the necessary information was collected to define if there is an influence of these digital communication media on young people in the sector, obtaining as a result that there is a medium high level of influence of these media on young people. As an experimental research design was used, and the methodology is exploratory-descriptive to carry out an analysis of said results and express them through graphs and tables and compare each of the responses.